THE EFFECTS OF GLOBALIZATION POLICIES IN GRAINS STRATEGIC TRADING IN SOME DEVELOPING COUNTRIES FOR THE PERIOD 1985-2012 - Kays Ghazal; Assad Ibrahim Al-Hayali (Mesopotamia Journal of Agriculture)
There was many Opinions that studied the impact of policies of economic globalization in the grain trade strategy in developing countries, some of these pointed out that the policies of globalization, a big benefit in the economies of developing countries and in the grain trade strategy in these countries as it helps them to see the international economic decision and increase the interest standard specifications as well as other benefits can be utilized in various economic fields. Other opinions pointed out that the policies of economic globalization worked to lower the share of grain exports strategy of developing its gross domestic product increased its imports which brings the rate of trade in non-interest of developing countries, the opposite of its impact on the poor distribution of national income on national and global levels, which increased the under development of developing countries and contributed to the progress of developed countries; In this regard our study adopted on the premise that the policies of economic globalization have different impacts in the grain trade strategy in developing countries by the nature of their economic structures and efficiency of their systems to deal with these policies, in order to prove the hypothesis of this search we studied on a sample of developing countries including (Egypt, Indonesia, Malaysia, Morocco, Tunisia, Turkey), where four strategy crops is (wheat, barley, rice, corn), had been selected and which has been relying on time-series data in the estimation of the phenomenon under Find and each country individually they reflect changes in the grain trade strategy according to their characteristics and attributes differ from one country to another.